(untitled) (Journal of Human Sciences, 2025)
This study entitled French diplomatic action tackles the democratic and electoral processes in Libya from 1952 to1965. Did France really help the Libyans or intervene for its own interests? As usual in the historical field, we will first go back to the past to understand how electoral trials began in Libya since the Italian era. Then, in a second step, it will be necessary to discuss the political change in Libya after the Second World War, particularly the municipal elections that were organized. France and Fezzan impacted the democratic process. Subsequently, we will open the debate around the elections of 1952, the first free elections in Libya as an independent state. Finally, we will examine politics and diplomatic actions towards parliamentary elections in Libya from 1956 to 1965. We will wonder whether France really acted for Fezzan or rather for its own country. We will come to our conclusions until new elements emerge as to the democratic elections in Libya during this period and the events surrounding it.